Torpid Mode: Hybrid of Sleep and Idle Mode as Power Saving Mechanism for IEEE 802.16j - Singh, Ashish; Potdar, Vidyasagar (IEEE Computer Society, 2010)
Sleep and Idle modes are proposed as power saving mechanisms in IEEE 802.16j Mobile Multi-hop Relay (MMR) networks. In this paper, these mechanisms are analyzed in terms of number of messages exchanged, latency and cost. Besides, hybridization of Sleep and Idle modes, named as Torpid mode is proposed as a power saving mechanism for IEEE 802.16j. Our proposed mechanism takes advantage of the relay stations. Analytical results verified by simulations evince that our proposed mechanism surpasses both Idle and Sleep modes significantly in terms of bandwidth consumption. Torpid mode also outperforms over the Idle mode in terms of latency and is superior to Sleep mode on the grounds of cost.